Marcos legais da instituição dos sistemas municipais de educação : fragmentos históricos - Lopes, Robson Vila Nova (2022)
In this article, outlined from a bibliographic and documentary review, it presents fragments of the historical process highlighting the legal frameworks of the institutionalization of Municipal Education Systems. The objective is to present a criticaldescriptive analysis of historical, political, conceptual and normative aspects that surround the discussion regarding the design of municipal education systems and their implications for educational policies in the context of the decentralization of responsibilities and obligations constitutionally attributed to municipalities. The research, in general, indicates that the constituent elements of educational policies cannot be understood by themselves, unrelated to the social materiality that concerns their significance. Therefore, the discussion about the autonomy of municipalities in the field of education is permeated by dissent.